A flexible self-charged power panel for harvesting and storing solar and mechanical energy. (November 2019) - Ma, Weiting; Li, Xinyi; Lu, Hongbo; Zhang, Maoqin; Yang, Xiaofei; Zhang, Tingting; Wu, Lifeng; Cao, Guozhong; Song, Weixing
Abstract: A flexible self-charged power panel is integrally designed and fabricated to simultaneously harvest solar and mechanical energy and convert and store in electric energy. The flexible amorphous silicon solar cell, the transparent triboelectric nanogenerator (TENG), and lithium (Li)-ion batteries are coherently integrated into one thin panel with the encapsulating materials, ethylene-tetra-fluoro-ethylene (ETFE) for the solar modules. The flexible self-charged power panel exhibits good performance to directly convert solar and mechanical energy into electricity that was directly stored in Li-ion battery without excessive energy loss. The integrated device also greatly minimizes the usage of current collectors, substrates and packaging materials. Moreover, such a power panel can compensate for the absence of solar cells and prolongs the time of energy supply and improve the energy density of the whole device. Graphical abstract: A flexible self-charged power panel is integrally designed and fabricated to simultaneously harvest solar and mechanical energy and convert and store in electric energy. The flexible amorphous silicon solar cell, the transparent triboelectric nanogenerator (TENG), and lithium ion batteries are coherently integrated into one thin panel with the encapsulating materials for the solar modules. The panel is fabricated by integrating Lithium-ion battery with solar cells and TENG to directly store the collected energy to avoid excess energy loss as well as to minimize the usage of current collectors, substrates and packaging materials. Image 1 Highlights: Our finding establishes a flexible self-charged power panel to harvest and store solar and mechanical energy. The integrated device greatly minimizes the usage of current collectors, substrates and packaging materials. The self-charged power panel provides a possible way to realize flexible self-powered system in wearable electronics.